Cities and Tasks - Hans R.A. Koster; Ceren Ozgen (Institute of Labor Economics (IZA), 2021)
This paper explores the relationship between routine-biased technological change and agglomeration economies. Using administrative data from the Netherlands, we first show that in dense areas, jobs are less routine-task intensive (i.e. less repetitive and automatable), meaning that jobs cover a larger spectrum of tasks. We then explore how the routine intensity of jobs affects the urban wage premium. We find that the urban wage premium is higher for workers performing non-routine tasks, particularly analytic tasks, while it is absent for workers in routine task intensive jobs. These findings also hold within skill groups and suggest that routinisation increases spatial wage and skill inequality within urban areas. We further provide suggestive evidence that a better matching of skills to jobs and increased learning opportunities in cities can explain these findings.
Keywords: R30; R33; 330; routinisation; tasks; agglomeration economies; employment density; skills mismatch